2018
DOI: 10.1055/a-0651-0424
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Fetal Growth Delay During Late Pregnancy After Maternal Gastric Bypass Surgery

Abstract: Purpose To investigate intrauterine fetal growth development and birth anthropometry of fetuses conceived after maternal gastric bypass surgery. Materials and Methods Longitudinal cohort study describing longitudinal growth estimated by ultrasound on 43 singleton pregnancies after gastric bypass compared to 43 BMI-matched controls. Results In fetuses after maternal gastric bypass surgery, growth percentiles decreased markedly from the beginning of the second trimester until the end of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“…The association between GB and SGA fetuses has been previously reported and discussed [4,6]. In addition to these observations, we recently observed markedly decreasing growth curves from the beginning of the second trimester until the end of pregnancy with the largest effect on the abdominal circumference [8]. While the mechanisms beyond these findings are not clarified yet, we assume that development of SGA offspring may be related to metabolic as well as micronutrient deficiencies, which commonly occurred in women after bariatric surgery and especially during pregnancy [6,13].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The association between GB and SGA fetuses has been previously reported and discussed [4,6]. In addition to these observations, we recently observed markedly decreasing growth curves from the beginning of the second trimester until the end of pregnancy with the largest effect on the abdominal circumference [8]. While the mechanisms beyond these findings are not clarified yet, we assume that development of SGA offspring may be related to metabolic as well as micronutrient deficiencies, which commonly occurred in women after bariatric surgery and especially during pregnancy [6,13].…”
Section: Discussionsupporting
confidence: 77%
“…Details of the study design are reported elsewhere [8]. In short, we retrospectively included 82 singleton pregnancies, 41 women after gastric bypass surgery (GB) and 41 BMI and agematched controls (BMIM), treated at our department between January 2007 and January 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of growth retardation in these fetuses is a topic of debate. A 2017 Austrian study found more pronounced hypoglycemia during an OGTT to be associated with reduced fetal abdominal circumference during the second trimester of pregnancy [ 62 ]. A 2020 prospective longitudinal study from the UK showed reduced fetal growth velocity starting in the third trimester, when compared to non-operated women with similar pre-pregnancy BMI [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, we demonstrated in previous studies a continuous decline in fetal growth throughout singleton pregnancy after bariatric surgery [5] and second a markedly decline of fetal subcutaneous adipose tissue thickness (FSCTT) of fetuses of mothers with a history of bariatric surgery [6]. Although the pathophysiological mechanisms remain unclear, it is believed that fetal growth restriction and low FSCTT are more likely caused by nutrient deficiency and by multifactorial genesis with altered metabolism as the most important factor, rather than by growth restriction due to placenta etiology or preeclampsia (PE) [7].…”
Section: Introductionmentioning
confidence: 94%